Supported depression self-care may prevent major depression in community-dwelling older adults with chronic physical conditions and co-morbid depressive symptoms. (20th February 2015) - Cole, Martin G.; McCusker, Jane; Yaffe, Mark; Strumpf, Erin; Sewitch, Maida; Sussman, Tamara; Ciampi, Antonio; Belzile, Eric
Abstract : Self-care programs for depression use educational and cognitive-behavioral techniques (e.g. written information, audiotapes, videotapes, computerized, or group courses) to assist patients in the management of depressive symptoms (Morgan and Jorm, 2008 ). In the UK, these interventions are recommended as step 1 in a stepped care program for treating depression in primary care (National Institute for Health and Clinical Excellence, 2007 ). One meta-analysis suggests that supported self-care (self-care with coaching) is more effective than unsupported self-care (Gellatly et al., 2007 ).